Formal encapsulation of [Fe(H2O)6]3+ by dinuclear {Fe2(hpdta)} units leads to a nonanuclear S = 13/2 Fe(III) oxo-cluster showing magnetic hysteresis - SCHMITT, WOLFGANG (My University, 2005)
Under solvothermal conditions the unprecedented nonanuclear Fe(III) aggregate [Fe9(mu3-O)4(mu-OH)4(hpdta)4]5- is formed through the formal encapsulation of [Fe(H2O)6]3+ by four [Fe2(hpdta)(H2O)2]+ units: the aggregates have ground state spins of S= 13/2 while the observed hysteresis below 1.8 K results from inter-cluster antiferromagnetic coupling.
PUBLISHED
Keywords: Chemistry